Occurrence of Intestinal Parasitic Contamination in Select Consumed Local Raw Vegetables and Fruits in Kuantan, Pahang - Afzan Mat Yusof,; Mardhiah Mohammad,; Muna Abshir Abdullahi,; Zeehaida Mohamed,; Robaiza Zakaria,; Ridhwan Abdul Wahab, (Tropical Life Sciences Research, 2017)
Intestinal parasitic infections are one of the most common causes of human diseases that result in serious health and economic issues in many developing and developed countries. Raw vegetables and fruits play an important role in transmitting parasites to humans. Hence, the aim of this study was to investigate the parasitological contamination of select commonly consumed local leafy vegetables and fruits in Kuantan, Malaysia. One kilogram of locally consumed raw vegetables and fruits were collected randomly from the Kuantan wet market (Pasar Tani) during the monsoon season (November 2014–January 2015) and the dry season (February 2015–April 2015). A standard wet mount procedure and modified Ziehl-Neelsen staining were used for the detection of parasites. In the present study, the examination of vegetables revealed five different parasite species. The vegetable samples collected from Kuantan’s wet market were positive for both helminthes and protozoa. However, the fruits samples were negative for parasitic contamination. Pegaga was the most contaminated leafy vegetable in this study, and Strongyloides was the parasite found most frequently. Furthermore, there was a high diversity in the type of parasites observed during the dry season compared to the monsoon season. Therefore, further action should be taken to reduce the occurrence of parasitic contamination in vegetables by implementing the principles of good agricultural practice and improving water treatment efficacy. Jangkitan parasit usus adalah salah satu penyakit manusia yang lazimnya menyebabkan masalah kesihatan yang serius dan mengakibatkan isu-isu ekonomi di negara-negara maju dan membangun. Sayur-sayuran mentah dan buah-buahan memainkan peranan yang penting sebagai medium jangkitan parasit ke dalam manusia. Oleh itu, tujuan kajian ini adalah untuk menyiasat pencemaran parasitologi daripada sayur-sayuran berdaun dan buah-buahan yang biasa dimakan serta dipilih penduduk tempatan di Kuantan, Malaysia. Sebanyak satu kilogram sayur-sayuran tempatan yang dimakan mentah dan buah-buahan telah dikumpulkan secara rawak dari pasar basah Kuantan (Pasar Tani) semasa musim tengkujuh (November 2014–Januari 2015) dan musim kering (Februari 2015–April 2015). Prosedur lazim “wet mount” dan teknik perwarnaan Ziehl-Neelsen yang dimodifikasi telah digunakan untuk mengesan parasit. Dalam kajian ini, pemeriksaan sayur-sayuran mendedahkan lima spesies parasite yang berbeza. Sampel sayur-sayuran yang diambil daripada pasar basah Kuantan adalah positif untuk kedua-dua helmin dan protozoa. Walau bagaimanapun, sampel buah-buahan adalah negatif untuk pencemaran parasit. Pegaga merupakan sayuran yang paling tercemar dalam kajian ini dan Strongyloides adalah parasit yang paling kerap ditemui. Tambahan pula, terdapat kepelbagaian yang tinggi dalam jenis parasit yang telah diperhatikan semasa musim kering berbanding musim tengkujuh. Oleh itu, tindakan lanjut perlu diambil untuk mengurangkan berlakunya pencemaran parasit didalam sayur-sayuran dengan melaksanakan prinsip-prinsip amalan pertanian yang baik serta keberkesanan rawatan air perlu dipertingkatkan.